Oblikovanje sodne prakse po uveljavitvi ZDR-1 - Robnik, Ivan (Podjetje in delo, 2015)
The article discusses the case law of the Supreme Court of the Republic of Slovenia and some final decisions and judgments of the Higher Labour and Social Court of the Republic of Slovenia in labour disputes after the entry into force of the Employment Relationship Act (ZDR-1) in April 2013. The formation of the case law based on the amended and new provisions of ZDR-1 has been gradual. However, courts have already interpreted some important provisions which have been amended by ZDR-1, namely on tenor of employment contract termination, protection of employees soon to be retired, court termination of employment contract and on some other notable issues.
Keywords: delodajalci; delovna razmerja; delovni spor; odpoved; pogodba o zaposlitvi; prenehanje; zaposleni